Reconfigurable control design with integration of a reference governor and reliability indicators - Weber, Philippe; Boussaid, Boumedyen; Khelassi, Ahmed; Theilliol, Didier; Aubrun, Christophe (Zielona Góra: Uniwersytet Zielonogórski)
A new approach to manage actuator redundancy in the presence of faults is proposed based on reliability indicators and a reference governor. The aim is to preserve the health of the actuators and the availability of the system both in the nominal behavior and in the presence of actuator faults. The use of reference governor control allocation is a solution to distribute the control efforts among a redundant set of actuators. In a degraded situation, a reconfigured control allocation strategy is proposed based on on-line re-estimation of the actuator reliabilit
Keywords: fault tolerant control systems; control allocation; reliability estimation; performance degradation; reference governor